Sistem Pendukung Keputusan Penentuan Pelanggan Terbaik Menggunakan Profile Matching - A. Ferico Octaviansyah Pasaribu; Nuroji Nuroji (Journal of Data Science and Information Systems, 2023)
The purpose of this study is to determine the best customer from the customer loyalty indicator which will measure the extent to which customer loyalty is formed by the company's efforts. So that other customers become more motivated from the rewards given by the company for determining the best customer. The best customer decision support system assists companies in automation and computerization in determining the best customers based on criteria set by the company. The results of data collection obtained the criteria used in determining the best customer, namely total payments, purchase frequency, and type of payment. The results for determining the best customer for rank 1 were obtained by a customer named Sri Widianingsih with a final score of 3.04. Rank 2 was obtained by a customer with the name Ahmad Budiantoro with a final score of 2.9175. Rank 3 is obtained by a customer with the name Kusumaningrum with a final score of 2.5975.